Website-Based Digital Marketing and Digital Branding as a Strategy to Increase Ecoprint Product Sales at Tembindigo MSME - Triyanto Triyanto; Nur Kholifah; Chytra Mahanani; Desnanda Putri Sagita; Fitria Oktariani; Muhammad Nurtanto (Jurnal Medika: Medika, 2025)
Tembindigo MSME, a natural textile-based enterprise, faces challenges in expanding its market reach due to limited digital marketing strategies and the absence of an integrated branding platform. The primary issue lies in the lack of a professional website and a consistent digital content management system, which hinders market penetration both nationally and internationally. This community engagement project aims to design and develop a professional website as the center of digital marketing, optimize digital marketing strategies, and enhance visual appeal through product storytelling. The method employed is Participatory Action Research (PAR), which involves the business owner and three employees across three stages: website development, social media optimization, and visual content enhancement. The success indicators include the availability of core features, integration of social media, and validation of visual and storytelling content. The main findings reveal that the website significantly increased business exposure, as evidenced by a spike in visitor traffic and a rise in sales of accessory products and workshop services. Specifically, visual consistency, narrative clarity, and ease of ordering were key factors in attracting new customers. The results of this activity provide practical insights for other ecoprint-based MSMEs seeking to adopt a structured, integrated, and locally rooted website-based digital branding strategy in response to digital transformation.